Second language learners' self-perceived roles and participation in face-to-face english writing consultations. (December 2016) - Lee, Cynthia
Abstract: Learner talk, a neglected area of study in the literature of language advising for second language (L2) learners, deserves more attention. With reference to multiple qualitative sources of data obtained from interviews and tutor-learner recorded conversations, this paper delineates learners' behaviors, strategies and contribution to language learning in tutor-dominant writing consultations. More importantly, it reveals the relationships between self-perception and learning behaviors via learning strategies. Nine native and non-native English-speaking writing tutors and 23 L2 learners from different disciplines participated in the study. Three types of L2 learners and 11 learning strategies were identified and analyzed based on the self-reported data and transcribed conversations. Analysis showed that the identified strategies signify the learners' behaviors and varied degrees of readiness to engage actively in learning by obtaining language input from tutors through some self-initiated acts, demonstrating selfawareness of their problems and establishing rapport with tutors to accomplish the learning task. Implications for teaching and future research are discussed.